Irrelevant player? The Commission’s role during the Eurozone crisis - Isabel Camisão (Journal of Contemporary European Research, 2015)
Under the EU treaties, provisions for collective (or institutional) forms of political leadership prevail over those made for leadership performed by individuals. Thus, an important leadership input from the EU’s institutions, namely the European Commission, would be expectable, particularly in times of crisis. Although not having the formal power of decision, the monopoly of initiative gives the Commission a considerable ability to influence the course of EU policymaking and overall the integration process. Moreover, the Commission has learned to maximize (and to create) windows of opportunity to act by cleverly using its resources (for example, its privileged access to information and expertise). However, during the current Eurozone crisis, the role of the Commission was overshadowed by the visibility and prominence of some national leaders and other institutions. What was the role of the Commission in the economic and financial crisis? Did the Commission influence the crisis responses agreed by the Member States? This article will answer these questions by analysing the European Commission’s main crisis response activities between 2008-2013. The central hypothesis of this paper is that the Commission actually played an important role in crisis response.